DEVELOPMENT OF SUSTAINABLE TOURISM DESTINATIONS TO INCREASE TOURIST ATTRACTIVENESS FROM THE QUINTUPLE HELIX PERSPECTIVE IN SINJAI DISTRICT - Firdaus, Firdaus; Titing, Andry Stepahnie; Badia, Juslan (Sosiohumaniora, 2025)
This study aims to describe the development of sustainable tourism destinations in Sinjai Regency and analyze the roles of actors within the Quintuple Helix framework. Utilizing a descriptive qualitative approach, data is collected through observation, in-depth interviews, and document analysis, which are then analyzed interactively. The results indicate that implementing the Quintuple Helix concept positively impacts tourist attraction, as the synergy among government, academics, business actors, civil society, and the environment strengthens the tourism ecosystem. Innovation in facilities, including accommodation and accessibility, is crucial for enhancing tourist appeal. However, challenges related to infrastructure and competition with privately managed attractions must be addressed to achieve optimal development. Effective management of tourist sites is essential for supporting local businesses. Tourism development has the potential to improve community welfare through economic growth, relying on cooperation among stakeholders, capacity building, and sustainable resource management. Increased training for business actors and responsive policies from the Tourism and Culture Office are necessary. By involving all elements of the Quintuple Helix approach and adhering to sustainability principles, Sinjai Regency can become an attractive tourist destination that enhances community welfare while supporting cultural and environmental preservation. Future research should analyze the influence of sustainable tourism on the economic, social, and environmental aspects of the local community to provide recommendations for formulating more effective sustainable development policies and programs.